Pengaruh Karakteristik Lansia Terhadap Tingkat Literasi Kesehatan Pasien Hipertensi di Puskesmas Sumbang 1 Kabupaten Banyumas - Putri, Dwi Rizki Ramadina; Susanti, Indri Heri; Yanti, Linda (STIKES Suaka Insan, 2023)
Low health literacy has the impact of having difficulty in understanding the procedures or health services that must be carried out. The purpose of this study was to determine the effect of elderly characteristics on the level of health literacy of hypertensive patients at Puskesmas Sumbang 1, Banyumas Regency. This type of research was using quantitative research with Chi-Square data analysis. The approach used in this study was a cross-sectional approach. The sampling method used a total sampling of 51 elderly people with hypertension. Data were collected by filling out the Health Literacy Scale European Union 16 Question (HLS-EU-Q16) questionnaire. The results showed that there was an influence of elderly characteristics on the level of health literacy consisting of age and gender so that the level of health literacy of the elderly at Puskesmas Sumbang 1 Banyumas Regency was in the adequate category